Why Researchers Use Academic Social Networking Sites (ASNS)? A Uses and Gratifications Approachâ€ - Omar Safori, Amjad (International Journal of Engineering and Technology, 2018)
In the academic world, the patterns of information sharing and publication are revolutionized by the use of Academic Social Networking Sites (ASNS). These platforms have influenced the dynamics and structure of research community by interrelating the scholars across the globe. Additionally, they provide platforms for professional communications, track the published research, sharing abstracts, uploading articles and providing links to the published articles. The purpose of this study is to investigate gratification and uses that faculty member derive from the use of social networks such as Academia.edu, Google Scholar, Research Gate, by employing uses and gratification theory. The focused group for this study were faculty members of 5 universities in Jordan. Results of this study show that ASNS are mainly used for consumption of information, with less focus on professional communication and information sharing. Gratifications are meaningful motivations for researchers to use ASNS and focus mainly on Self-promotion, acquisition of professional knowledge, interaction with peers and peer community. Â